PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA KOBER MIE SETAN (STUDY KASUS KOBER MIE SETAN PEGUYANGAN) - I Ketut Sudana; Ni Luh Putu Yesy Anggreni; I Putu Eka Indrawan (Widyadari : Jurnal Pendidikan, 2021)
Currently the culinary business is a promising business, even in this pandemic situation many people are turning to the culinary business. One of the spicy food culinary in Indonesia is Kober Mie Setan. Kober Mie Setan is famous for offering spicy noodle dishes based on the level chosen by the customer. The purpose of this study was to determine: (1) the effect of service quality on purchasing decisions at Kober Mie Setan (Case Study of Kober Mie Setan Peguyangan); (2) The Influence of Price on Purchase Decisions on Kober Mie Setan (Case Study of Kober Mie Setan Peguyangan); (3) The Effect of Service Quality and Price. Together on Purchase Decisions at Kober Mie Setan (Case Study of Kober Mie Setan Peguyangan). Data were analyzed by statistical analysis of simple linear regression and multiple linear regression with two predictors. Through the prediction results with predictors X1 (Service Quality) and X2 (Price) to Y (Purchase Decision), the Freg price is 33.21. With (N-m-1) in this case db = 93/2, with a significance level of 5%, the Ftable value is 3.09. This means that the regression line analyzed is significant to be used as a basis for prediction because there is a significant relationship between the criteria (Y) and the predictors (X1, X2). Freg is greater than the F table value or 33.21 > 3.09. Shows that there is a significant relationship between Service Quality and Price on Purchase Decisions at Kober Mie Setan (Case Study of Kober Mie Setan Peguyangan)